Practical solutions to aflatoxins - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 2005)
Dr Benjani Theu, Malawi?s national coordinator for plant protection, explains what aflatoxins are, and what farmers can do to prevent the growth of the fungi that produce them.